2018
DOI: 10.1371/journal.pone.0202582
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic analysis of aquaculture salmonid populations in China using a 57K rainbow trout SNP array

Abstract: Various salmonid species are cultivated in cold water aquaculture. However, due to limited genomic data resources, specific high-throughput genotyping tools are not available to many of the salmonid species. In this study, a 57K single nucleotide polymorphism (SNP) array for rainbow trout (Oncorhynchus mykiss) was utilized to detect polymorphisms in seven salmonid species, including Hucho taimen, Oncorhynchus masou, Salvelinus fontinalis, Brachymystax lenok, Salvelinus leucomaenis, O. kisutch, and O. mykiss. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In general, farmed stocks have the tendency to show reduced genetic variability over generations due to artificial selection and a reduced number of breeders in the initial base population [11,46,47,48]. Therefore, it is important to evaluate how the genetic diversity can be maintained when considering the possibility of bottleneck events due to the low effective population size shown in fish farms.…”
Section: Discussionmentioning
confidence: 99%
“…In general, farmed stocks have the tendency to show reduced genetic variability over generations due to artificial selection and a reduced number of breeders in the initial base population [11,46,47,48]. Therefore, it is important to evaluate how the genetic diversity can be maintained when considering the possibility of bottleneck events due to the low effective population size shown in fish farms.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of approximately 900 polymorphic sites facilitated studying the genetic structure of wild Mediterranean brown trout populations in Italy and to begin the selection of native broodstocks. Zhang et al [62] used a 57K DNA chip developed for rainbow trout in different salmonid species, and Drywa et al [63] used a SNP array developed for Atlantic salmon to analyze a population of lake brown trout (S. trutta trutta).…”
Section: Next Generation Sequencing (Ngs)mentioning
confidence: 99%
“…Various high-density SNP chips have been developed in recent years for many model species, including commercially important salmonid species, such as rainbow trout and Atlantic salmon [ 38 , 39 , 40 , 41 ]. Despite the limited genomic data resources available for other salmonids, the high sequence similarity between them has indicated that SNP microarrays may be suitable for the study of any member of this fish family, trout included [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%